Robust optimal dispatching model and a benefit allocation strategy for rural novel virtual power plants incorporating biomass waste energy conversion and carbon cycle utilization - Ju, Liwei; Zhou, Qingqing; Pan, Miao; Wei, Wanting; Wang, Yi; Sun, Jie; Pan, Yushu (Frontiers in Energy Research, 2023)
To optimize the utilization of the rural biomass waste resources like straw, solid waste, biomass waste energy conversion (BWEC) and carbon cycle utilization (CCU) are integrated into traditional virtual power plant, namely, rural BWEC-CCU-based virtual power plant (BECU-VPP).Further, a fuzzy robust two-stage dispatching optimal model for BECU-VPP is established considering the nondeterminacy from wind power plant (WPP) and photovoltaic (PV).The scheduling model includes the day-ahead deterministic dispatching model and real-time uncertainty dispatching model. Among them, in day-ahead dispatching phrase,the dispatching plan is formulated with minimum operating cost and carbon emission targets.And in real-time dispatching phrase, the optimal dispatching strategy is formulated with aim at minimum deviation adjustment cost by applying the Latin hypercube sampling method and the robust stochastic theory are used to describe the uncertainty.Thirdly, in order to achieve the optimal distribution of multi-agent cooperation benefit,a benefit distribution strategy based on Nash Negotiation is designed considering three-dimensional interfering factor of the marginal benefit contribution,carbon emission contribution and deviation risk. Finally,a rural distribution network in Jiangsu province,China is selected for case analysis, and the results show that: (1)The synergistic optimal effect of BWEC and CCU is obvious, the operation cost and deviation adjustment cost could decrease by 26.21% and 39.78%, respectively.While the capacity ratio of WPP+PV, BWEC, and CCU is 5:3:2,the dispatching scheme is optimum.(2)This scheduling model can be used to formulate the optimal scheduling scheme.Compared with the robust coefficient Γ=0, when Γ=1, the WPP and PV output decreased by 15.72% and 15.12%, and the output of BWEC and CCU increased by 30.7% and 188.19%. When Γ∈ [0.3, 0.9), the growth of Γ has the most direct impact on the dispatching scheme.(3)The proposed benefit equilibrium allocation strategy can formulate the most reasonable benefits allocation plan. Compared with the traditional benefit allocation strategy, when the proposed method is used, the benefit share of WPP and PV reduces by 5.2%,and the benefit share of SHS, BWEC and CCU increase by 1.7%,9.7% and 3.8%,respectively.Overall,the proposed optimal dispatching and benefit allocation strategy could improve the aggregated utilization of rural biomass waste resources and distributed energy resources while balancing the benefit appeal of different agents.